2018
DOI: 10.1123/jcsp.2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Passion, Basic Psychological Needs Satisfaction and Athlete Burnout: Examining Direct and Indirect Effects

Abstract: Athlete burnout symptoms are detrimental to athlete well-being (Cresswell & Eklund, 2005). Obsessive passion has been identified as an antecedent of athlete burnout, with basic psychological need satisfaction potentially mediating this process (Curran et al., 2011; 2013; Deci & Ryan, 2000; Vallerand et al., 2003). The aim of the current research was to extend on previous work (e.g., Curran et al., 2011; 2013; Gustafsson et al., 2011) and examine whether the relationship between passion and athlete burnout was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 73 publications
4
18
0
1
Order By: Relevance
“…This effect could be explained by the nature of the BPN, for example, when athletes feel more competent, they firmly believe they can achieve good results, an attitude contrary to burnout, in which athletes do not feel capable of achieving their goals because of a very much reduced sense of achievement [62]. Additionally, a significant negative impact on the perceptions of competence can influence the value that athletes assign to their sport [63]. When they feel less autonomous, the lack of psychological freedom could bring about them to run out of external resources causing an imbalance between demands and resources.…”
Section: Relationship Between Satisfaction Of Bpn and Burnout And Engmentioning
confidence: 99%
“…This effect could be explained by the nature of the BPN, for example, when athletes feel more competent, they firmly believe they can achieve good results, an attitude contrary to burnout, in which athletes do not feel capable of achieving their goals because of a very much reduced sense of achievement [62]. Additionally, a significant negative impact on the perceptions of competence can influence the value that athletes assign to their sport [63]. When they feel less autonomous, the lack of psychological freedom could bring about them to run out of external resources causing an imbalance between demands and resources.…”
Section: Relationship Between Satisfaction Of Bpn and Burnout And Engmentioning
confidence: 99%
“…Another variable that resulted mediated by the social support was the harmonious passion, which, as with positivity, presented direct and indirect effects statistically regarding the burnout. This result was expected, due to the different studies that have found that the harmonious passion is a significant predictor of burnout [27,72]. Regarding the obsessive passion, it was not measured by the social support but it did obtain a positive direct and significant effect with the burnout.…”
Section: Discussionmentioning
confidence: 60%
“…Another variable that resulted mediated by the social support was the harmonious passion that, same as positivity, presented direct and indirect effects statistically regarding the burnout. This result was expected, due to the different studies that have found that the harmonious passion is a significant predictor of burnout [27,50]. Regarding the obsessive passion, it was not measured by the social support but it did obtain a positive direct and significant effect with the burnout.…”
Section: Discussionmentioning
confidence: 60%